Problem Based Learning: Implementation of Bioentrepreneurship Learning to Increase Student Interest in Biotechnology Materials - Slamet Santosa; Dewi Puspita Sari; Chanafia Yusfi Chotimah; Sukamti Sukamti (Postgraduate, University of Mataram, 2023)
The purpose of this study is to increase the interest in learning students. This research is a Classroom Action Research that is carried out in two cycles. Each cycle has four stages which include planning, implementation, observation, and reflection. The subjects of this study were students of class XII MIPA 3 which totaled 29 students. Data sources are obtained from teachers and learners by observation, interviews, and documentation. The triangulation method is used to validate the data and analyze the data using qualitative descriptive techniques. The results showed that student’s interest in learning increased from pre-action to cycle II. Indicators of feelings of pleasure and interest in learning increased by 21.55% from pre-action to cycle II, indicators there was active participation increased by 25.00% from pre-action to cycle II, indicators there was a tendency to pay attention and great concentration power increased by 22.50% from pre-action to cycle II, indicators had positive feelings and a willingness to learn that always increased by 26.74% from pre-action to cycle II. Based on the research that has been carried out, it can be concluded that problem-based bio-entrepreneurship learning can increase the interest in learning students XII MIPA 3 on biotechnology materials.